A Three Dimensional Gas-Kinetic Scheme with Moving Mesh for Low-Speed Viscous Flow Computations (Advances in Applied Mathematics and Mechanics, 2021)
The paper introduces the gas-kinetic scheme for three-dimensional (3D) flow simulation. First, under a unified coordinate transformation, the 3D gas-kinetic BGK equation is transformed intoa computational space with arbitrary mesh moving velocity. Second,based on the Chapman-Enskog expansion of the kinetic equation, alocal solution of gas distribution function is constructed and usedin a finite volume scheme. As a result, a Navier-Stokes flow solveris developed for the low speed flow computation with dynamical meshmovement. Several test cases are used to validate the 3D gas-kineticmethod. The first example is a 3D cavity flow with up-movingboundary at Reynolds number $3200$, where the periodic solutions arecompared with the experimental measurements. Then, the flowevolution inside a rotating 3D cavity is simulated with the movingmesh method, where the solution differences between 2D and 3Dsimulation are explicitly presented. Finally, the scheme is appliedto the falling plate study, where the unsteady plate tumbling motioninside water tank has been studied and compared with theexperimental measurements.